Global, regional, and national burden of 34 cancer groups across 204 countries and territories, 1990–2021, and projections to 2050: a systematic analysis of the Global Burden of Disease Study 2021 - Zhu, Linfeng; Zhu, Jiangpeng; Wang, Qing; Sun, Xiaotong; Yuan, YuTao; Ding, Sheng; Zhao, Jiafeng; Liu, Lei; Hou, Shuangshuang (Frontiers in Oncology, 2025)
IntroductionDetailed, comprehensive, and timely reporting on cancer incidence, mortality, and associated burdens is essential for understanding the evolving trends of this complex disease. This study aims to evaluate the burdens of 34 types of cancer across 204 countries and territories from 1990 to 2021, incorporating the latest epidemiological data to provide a framework for policy discussions, resource allocation, and research prioritization.MethodsUsing data from the Global Burden of Disease (GBD) 2021 study, we analyzed 34 cancer types across 204 countries from 1990 to 2021, stratifying by age, sex, region, and sociodemographic index (SDI) and projecting future trends using a Bayesian age-period-cohort model.ResultsIn 2021, there were 23.57 million new cases and 9.83 million deaths, with a global age-standardized incidence rate (ASIR) of 275.2 per 100,000 and age-standardized mortality rate (ASMR) of 115.8 per 100,000. Cancer incidence has risen 2.3-fold, with the ASIR increasing by 8.8% and the ASMR decreasing by 21.5% over the period since 1990. Tracheal, bronchial, and lung cancer, colorectal cancer, stomach cancer, and breast cancer were the leading causes of mortality, while nonmelanoma skin cancer, tracheal, bronchial, and lung cancer, colorectal cancer, breast cancer, and prostate cancer had the highest incidence rates. Men had 1.2 times higher incidence and 1.3 times higher mortality than women. North America had the highest ASIR, while East Africa had the highest ASMR. High-SDI countries had higher incidence, whereas low-SDI countries bore the highest mortality burden. By 2050, cancer incidence is projected to exceed 26 million cases, with prevalence surpassing 100 million, while mortality is expected to decline by 14.8%.ConclusionsDespite advances in detection and treatment, the rising global cancer burden and persistent disparities highlight the urgent need for equitable prevention, early diagnosis, and resource allocation to reduce cancer mortality worldwide. The potential long-term impact of COVID-19 on cancer development and progression remains unclear, warranting further investigation in the post-pandemic era.